Implementing the South African Additive Manufacturing Technology Roadmap - the role of an Additive Manufacturing Centre of Competence - Du Preez, W.B.; De Beer, D.J. (South African Journal of Industrial Engineering, 2015)
The Rapid Product Development Association of South Africa (RAPDASA) expressed the need for a national Additive Manufacturing Roadmap. Consequentially, the South African Department of Science and Technology commissioned the development of a South African Additive Manufacturing Technology Roadmap. This was intended to guide role-players in identifying business opportunities, addressing technology gaps, focusing development programmes, and informing investment decisions that would enable local companies and industry sectors to become global leaders in selected areas of additive manufacturing. The challenge remains now for South Africa to decide on an implementation approach that will maximize the impact in the shortest possible time. This article introduces the concept of a national Additive Manufacturing Centre of Competence (AMCoC) as a primary implementation vehicle for the roadmap. The support of the current leading players in additive manufacturing in South Africa for such a centre of competence is shared and their key roles are indicated. A summary of the investments that the leading players have already made in the focus areas of the AMCoC over the past two decades is given as confirmation of their commitment towards the advancement of the additive manufacturing technology. An exposition is given of how the AMCoC could indeed become the primary initiative for achieving the agreed national goals on additive manufacturing. The conclusion is that investment by public and private institutions in an AMCoC would be the next step towards ensuring South Africa's continued progress in the field. Die "Rapid Product Development Association of South Africa" (RAPDASA) het die behoefte aan 'n nasionale toevoegingsvervaardigingpadkaart uitgelig. Gevolglik het die Departement van Wetenskap en Tegnologie opdrag vir die ontwikkel van so 'n padkaart gegee. Hierdie was veronderstel om rolspelers te lei in die identifisering van besigheidsgeleenthede, die aanspreek van tegnologie tekortkominge, die fokus op ontwikkelingsprogramme en om beleggingsbesluite te beïnvloed wat plaaslike maatskappye en industrieë in staat sal stel om wêreldleiers op uitgekose areas van toevoegingsvervaardiging te word. Die uitdaging vir Suid-Afrika is nou op 'n toepassingsbenadering wat die maksimum impak in die kortste moontlike tyd sal verseker. Hierdie artikel stel die konsep van 'n nasionale Toevoegings-vervaardiging Sentrum van Bevoegdheid as 'n primêre toepassing van die padkaart voor. Die ondersteuning deur die hoof rolspelers in Suid-Afrika vir so 'n sentrum word gedeel en hulle onderskeie rolle is aangedui. Die rolspelers se toewyding word gestaaf aan die hand van hul beleggings in die fokus areas van die Sentrum oor die laaste twee dekades. 'n Uiteensetting word verskaf van hoe die Sentrum inderdaad die hoof inisiatief vir die behaal van die ooreengekome nasionale doelstellings kan word. Die gevolgtrekking is dat belegging deur die publieke en privaat instansies in so 'n sentrum die volgende stap tot die versekering van Suid-Afrika se voortgesette vordering in veld is.